Preliminary Evidence for Domestication Effects on the Genetic Diversity of Guazuma crinita in the Peruvian Amazon - Tuisima Coral, Lady Laura (2020)
Guazuma crinita, a fast-growing timber tree species, was chosen for domestication in the Peruvian Amazon because it can be harvested at an early age and it contributes to the livelihood of local farmers. Although it is in an early stage of domestication, we do not know the impact of the domestication process on its genetic resources. Amplified fragment length polymorphic (AFLP) fingerprints were used to estimate the genetic diversity of G. crinita populations in different stages of domestication. Our objectives were (i) to estimate the level of genetic diversity in G. crinita using AFLP markers, (ii) to describe how the genetic diversity is distributed within and among populations and provenances, and (iii) to assess the genetic diversity in naturally regenerated, cultivated and semi-domesticated populations. We generated fingerprints for 58 leaf samples representing eight provenances and the three population types. We used seven selective primer combinations. A total of 171 fragments were amplified with 99.4% polymorphism at the species level. Nei’s genetic diversity and Shannon information index were slightly higher in the naturally regenerated population than in the cultivated and semi-domesticated populations (He = 0.10, 0.09 and 0.09; I = 0.19, 0.15 and 0.16, respectively). The analysis of molecular variation showed higher genetic diversity within rather than among provenances (84% and 4%, respectively). Cluster analysis (unweighted pair group method with arithmetic mean) and principal coordinate analysis did not show correspondence between genetic and geographic distance. There was significant genetic differentiation among population types (Fst = 0.12 at p < 0.001). The sample size was small, so the results are considered as preliminary, pending further research with larger sample sizes. Nevertheless, these results suggest that domestication has a slight but significant effect on the diversity levels of G. crinita and this should be considered when planning a domestication program.